AB0475 CLINICAL RELEVANCE OF CLINICOPATHOLOGICAL PHENOTYPE AND ANTIBODY SPECIFICITY IN ANCA-ASSOCIATED VASCULITIS. (2nd June 2020) - Fernandes Serodio, J.; Prieto-González, S.; Espígol-Frigolé, G.; Alba, M.; Marco-Hernández, J.; Cid, M. C.; Hernández-Rodríguez, J.
Abstract : Background: Classification of ANCA-associated vasculitis (AAV) has emerged in order to identify more homogenous subgroups of patients with granulomatosis with polyangiitis (GPA) or microscopic polyangiitis (MPA). However, the exact value of classifying patients according to antibody specificity (proteinase 3 [PR3] or myeloperoxidase [MPO]) is still unclear. Objectives: To assess demographic, clinical and prognostic differences among subgroups of AAV patients, according to clinicopathological classification (GPA vs . MPA) and antibody specificity (PR3 vs . MPO) in a single-centre cohort. Methods: A clinical retrospective (1990-2019) observational analysis was performed. Among all patients with ANCA positivity, we analysed patients with GPA and MPA diagnosed according to 2018 Draft Classification Criteria for AAV 1, who were homogeneously treated and followed by the authors. Demographic, clinical and laboratory data, as well as disease outcomes, particularly BVAS, disease relapses and survival, were reviewed. Results: Among a total 140 patients with any form of AAV, 32 were excluded for a diagnosis of isolated interstitial lung disease (n=10), cocaine-induced AAV (n=3), ANCA negative or undetermined disease (n=16), atypical ANCA or double PR3/MPO positivity (n=3). Finally, 108 patients with MPA (n=66) or GPA (n=42) were included (83 MPO, 25 PR3). GPA was associated with PR3 in 55% and MPO 45% of patients. MPA was associated with MPO in 97% and PR3 in 3% of patients. GPA patients with PR3 or MPO presented with similar clinical features, disease extent and BVAS. However, compared with GPA/PR3, GPA/MPO were more frequently women (p=0.002). MPA patients presented more frequent with renal involvement (p=0.008) and GPA patients with ENT/ocular involvement (p<0.001). Patients with MPO were older (p=0.028) and more frequently women (p=0.001) than PR3 patients. When antibody specificity was compared, differences on organ-specific manifestations were less clear than between clinical phenotypes (GPA vs. MPA), and were only seen in ENT/ocular involvement (more frequent in PR3 than in MPO patients) and in muscle biopsies disclosing vasculitis (more frequent in MPO than in PR3 patients). GPA and PR3 patients presented more frequent relapsing disease than MPA and MPO patients, respectively (GPA 60% vs. MPA 36%; p=0.018 / PR3 60% vs. MPO 41%; p=0.094). While GPA tended to have a better survival rate than MPA patients (p=0.066) (Graph1), the MPO-associated disease (GPA or MPA) had clearly worse survival prognosis than PR3-AAV (p=0.008) (Graph2), similarly to what occurred in GPA-MPO (compared with GPA-PR3). Conclusion: A high proportion of GPA patients with MPO-ANCA (45%) is observed in our series. GPA is associated with a more frequent relapsing disease than MPA. MPA and presence of MPO were more frequent in females and older patients. Clinical features were similar in GPA patients with PR3 or MPO. The presence of MPO (in GPA or MPA) seems to be the main factor associated with mortality in AAV. References: [1]Robson JC, Grayson PC, Ponte C, et al. Draft classification criteria for the ANCA associated vasculitides. Ann Rheum Dis 2018;77 (suppl 2):60-1. Disclosure of Interests: João Fernandes Serodio: None declared, Sergio Prieto-González: None declared, Georgina Espígol-Frigolé: None declared, Marco Alba: None declared, Javier Marco-Hernández: None declared, Maria C. Cid Grant/research support from: Kiniksa Pharmaceuticals, Consultant of: Janssen, Abbvie, Roche, GSK, Speakers bureau: Vifor, José Hernández-Rodríguez: None declared